RESTORATIVE JUSTICE AS AN ALTERNATIVE TO SETTLEMENT OF MISDEMEANOR CRIMES: A CASE STUDY : KEADILAN RESTORATIF SEBAGAI ALTERNATIF PENYELESAIAN KEJAHATAN PELANGGARAN: STUDI KASUS - Athif Hasan Al Banna; Yusuf Saefudin; Syahrul Adam Salleh Ibrahim (Journal Presumption of Law, 2024)
This article examines the utilization of restorative justice as an alternative to misdemeanor crimes in the criminal justice system at the Police sector Purwareja Klampok level. The aim of this research is to analyze the effectiveness and challenges faced in implementing the principles of restorative justice to address criminal offenses at the Police sector level. This research adopts a normative juridical approach and utilizes both secondary and primary data sources. Secondary data is obtained through literature research, while primary data is gathered through observations and interviews, involving key stakeholders such as police officers, victims, offenders, and community members, to obtain a comprehensive understanding of the implementation of restorative justice in Police sector Purwareja Klampok. The findings of this study highlight the potential benefits of restorative justice in facilitating victim-offender reconciliation, involving the community, and promoting rehabilitation. Additionally, the research reveals limitations and barriers in the application of restorative justice, including limited resources, inadequate awareness and understanding among stakeholders, and the need for capacity development and training. Based on data analysis, this article provides recommendations to enhance the implementation of restorative justice at the Police sector Purwareja Klampok level. In conclusion, this research contributes to the existing literature on restorative justice by offering insights into its application as an alternative to misdemeanor crimes in the criminal justice system at the Police sector Purwareja Klampok level. The study emphasizes the importance of promoting a more balanced and comprehensive approach to justice that focuses on repairing harm, fostering accountability, and restoring social harmony within the community. Keywords: restorative justice, misdemeanor, implementation of restorative justice, social improvement, police sector.